REMARK ABOUT CHARACTERIZATION OF 2-INNER PRODUCT - Anevska, Katerina; Malčeski, Risto (Matematichki Bilten, 2016)
Characterization of 2-inner product is focus of interest of many mathematicians. In this paper proofs of two characterizations of 2-inner product, which are actually consequences of the Theorem 1 [15], are given. Also, generalizations of already know Hayashi (see [4], pg. 297) and Zarantonello ([5]) inequalities are fully elaborated.